Unlocking Investment Potential: Strategic Opportunities for Driving Investment in Tanzania’s Local Government Authorities - Shillingi, Venance; Landa, Elizabeth (Journal of Policy and Leadership, 2025)
Developing countries are on the verge of attracting investors locally and internationally, and Tanzania is no exception. Both central and local authorities in Tanzania are developing various strategies to attract investors to establish industries. The study examines the strategic opportunities available in Tanzania's local government authorities (LGAs) to attract investors to industrial development and the impact of government policies. It employs a mixed-methods design with a multistage sampling technique to select regions and Local Government Areas (LGAs). The unit of analysis was senior officials of the local governments (LGAs), and a sample of 67 respondents was selected. Reliability and validity tests were performed, while multiple linear regression was used to test the hypotheses. Content analysis was employed to analyse qualitative data, complementing the quantitative data. Results revealed that access to raw materials (β =2.179, p = 0.038), skilled human resources (β = 2.409, p = 0.050), and investment policies (β =5.26, p = 0.003) significantly influence investor attraction. In contrast, access to capital,infrastructure, and technology exhibited no significant effect. Overall, the model accounts for 46.9% of the variance in investor attraction, underscoring the significance of government policies and skilled labour in industrial development. The study concluded that raw materials, government investment policies, and skilled human resources significantly influence investor attraction in Tanzania’s local government areas (LGAs). It recommends strengthening government investment policies, enhancing skilled labour, and ensuring the availability of raw materials to promote industrial development.